Control of electron transfer in nitrogenase. (December 2018) - Seefeldt, Lance C; Peters, John W; Beratan, David N; Bothner, Brian; Minteer, Shelley D; Raugei, Simone; Hoffman, Brian M
Graphical abstract: Highlights: N2 reduction involves electron transfer events that are coupled to the hydrolysis of ATP. ATP hydrolysis occurs after electron transfer. The multiple electron transfer events likely occur by a deficit-spending sequential model. Energy transduction includes negative cooperativity across the nitrogenase complex. Abstract : The bacterial enzyme nitrogenase achieves the reduction of dinitrogen (N2 ) to ammonia (NH3 ) utilizing electrons, protons, and energy from the hydrolysis of ATP. Building on earlier foundational knowledge, recent studies provide molecular-level details on how the energy of ATP hydrolysis is utilized, the sequencing of multiple electron transfer events, and the nature of energy transduction across this large protein complex. Here, we review the state of knowledge about energy transduction in nitrogenase.